Metabolomics in Neurodegenerative Disease - Green, Brian (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The range of human neurodegenerative diseases continues to pose significant unmet medical needs for societies around the world. The progressive and terminal nature of these conditions places a considerable personal burden on the individual affected but also on public health systems and health services. Tens of millions of people are indiscriminately affected by various dementias, which are rising at an alarming rate. There are no cures for many conditions, and it is clear that treatments applied as early as possible could greatly improve outcomes for patients. Therefore, new disease classification and diagnostic tools should be a key priority. Metabolomics represents a relatively new field of analytical science, which can be extremely useful in the early diagnosis of disease. The relatively unique feature of metabolites is that they sit at the intersection between the genetic background of an organism and its environment. Because many neurodegenerative diseases are not genetically inherited (instead having a range of known genetic risk factors and also a large number of unknown environmental triggers) the field of metabolomics offers great promise for the discovery of new, biologically, and clinically relevant biomarkers for neurodegenerative disorders. It is already bringing forward new knowledge in terms of the mechanisms of neurodegenerative disease.